Strontium(II) Ion Surface-Imprinted Polymers Supported by Potassium Tetratitanate Whiskers: Synthesis, Characterization and Adsorption Behaviours - Chunxiang Li; Xiaojie Zhang; Jianming Pan; Pingping Xu; Yan Liu; Yongsheng Yan; Zulei Zhang (Adsorption Science & Technology, 2009)
Novel surface strontium(II) ion-imprinted adsorbent particles have been prepared via the copolymerization of chitosan as the monomer, γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560) as the cross-linking agent and 2,2′-azobisisobutyronitrile (AIBN) as the initiator in the presence of SrCl 2 • 6H 2 O. The prepared imprinted adsorbent was used for the selective solid-phase extraction (SPE) of trace Sr(II) ions in a practical sample prior to its determination by inductively coupled plasma–atomic emission spectrometry (ICP–AES). The results suggest that the adsorption kinetic data accorded better with the pseudo-second-order model, while the adsorption equilibrium data gave a good fit to the Langmuir isotherm equation, yielding a maximum adsorption capacity of 27.58 mg/g and a Langmuir adsorption equilibrium coefficient of 0.0363 ℓ/mg at 298 K. The relative selectivity coefficient values of Sr(II) ion-imprinted particles were several times greater than those for the non-imprinted matrix. The new Sr(II) ion-imprinted micro-beads were successfully applied for the separation of Sr(II) ions from river and clay samples. The detection limit (3σ) for Sr(II) ions as determined by flame atomic absorption spectrometry (FAAS) was 0.21 ng/mℓ. The relative standard deviation (RSD) for the determination of Sr(II) ions was 6–9% over the concentration range 0.03–0.3 mg/ℓ.